Produk Fermentasi Rumen dan Produksi Protein Mikroba Sapi Lokal yang Diberi Pakan Jerami Amoniasi dan Beberapa Bahan Pakan Sumber Energi - Novita Hindratiningrum; Muhamad Bata; Setya Agus Santosa (Jurnal Agripet, 2011)
Products of rumen fermentation and protein microbial of dairy cattle feed with rice bran ammonization and some feedstuffs as an energy sources